Effect of coupling agent on the properties of pineapple leaf fiber/ polypropylene composite - Nurul Farah Qurratu Aini, Ghani; Nurjannah, Salim; Nurul Huda, Abu Bakar; Rasidi, Roslan; Edy Sutjipto, Agus Geter (Trans Tech Publications, Switzerland, 2024)
Natural fibre matrix composites have been utilized in numerous industries, including the automotive, construction, and aerospace sectors. Maleic anhydride grafted polypropylene (MAPP) was used in this study to examine the effect of the coupling agent on the properties of a composite-produced using pineapple leaf fibre. The weight ratios of pineapple leaf fibre, polypropylene, and MAPP were 20g:180g, 15g:180g:5g, and 10g:180g:10g, respectively. The materials were mixed using a co-rotating twin-screw extruder machine at 170 °C and 50 rpm. The composite was then manufactured by injection molding at 185 °C. The mechanical and physical properties of PALF composite were examined by using a tensile test, impact test, and water absorption test. Thermal Gravimetric Analysis (TGA) was used to characterize the thermal properties of PALF/PP, and PALF/PP/MAPP composite. The surface morphology and fracture surface of the composite was characterized by using Scanning Electron Microscopy (SEM). Compared to the composite containing 5 g of MAPP, the tensile strength composite containing 10 g of MAPP produced a stronger interfacial bond. According to the impact test, adding more MAPP increases the material's strength and stress transmission. The average percentage of water absorption indicates low water absorption after the addition of the coupling agent. It can be concluded that the addition of a coupling agent improved the composite's properties.